The Importance of Feng Shui Influence on the Housing Selection Among the Chinese in Generation Y: A Study on the Developers' Perceptions - Shafii, Haryati; Pui Yi, Leong; Md Yassin, Azlina (Journal of Technology Management and Business, 2020)
Feng shui, an element that has been associated with success, wealth, and harmony, is often considered the key factor for the decision-making of housing purchase among the Chinese in Malaysia. Nevertheless, property developers often overlooked this factor, resulting in a gap between consumers' expectations and developers' perceptions, which could lead to customers' dissatisfaction. This study was carried out to identify the importance of feng shui theory towards housing development, determine the influence of feng shui factors in housing selection, and examine the perceptions of developers towards feng Shui factors in residential property. This paper adopted a qualitative approach by employing the interviewing technique. This study was conducted within a selected residential area in Sungai Petani, Kedah and the respondents were the Generation Y within the Chinese group. The results show that most of the developers believed that only rich and famous people are concerned about the feng shui element in selecting a residential property. Besides that, the construction of a housing project has to consider many factors prior the completion, including the multiracial customers as the potential buyers. Hence, it is not practical to consider the feng shui element for each person.